PD-1 Blockade Promotes Emerging Checkpoint Inhibitors in Enhancing T Cell Responses to Allogeneic Dendritic Cells - Stecher, Carmen; Battin, Claire; Leitner, Judith; Zettl, Markus; Grabmeier-Pfistershammer, Katharina; Höller, Christoph; Zlabinger, Gerhard J.; Steinberger, Peter (Frontiers in Immunology, 2017)
Immune checkpoint inhibitors, which target coinhibitory T cell molecules to promote anticancer immune responses, are on the rise to become a new pillar of cancer therapy. However, current immune checkpoint-based therapies are successful only in a subset of patients, and acquired resistances pose additional challenges. Finding new targets and combining checkpoint inhibitors might help to overcome these limitations. In this study, human T cells stimulated with allogeneic DC were used to compare immune checkpoint inhibitors targeting TIM-3, BTLA, LAG-3, CTLA 4 and TIGIT alone or in combination with a PD-1 antibody. We found that PD-1 blockade bears a unique potency to enhance T cell proliferation and cytokine production. Other checkpoint inhibitors failed to significantly augment T cell responses when used alone. However, antibodies to TIM 3, BTLA, LAG 3 and CTLA 4 enhanced T cell proliferation in presence of a PD-1 antibody. Upregulation of coinhibitory T cell receptors upon PD 1 blockade was identified as a potential mechanism for synergistic effects between checkpoint inhibitors. Donor-specific variation in response to immune checkpoint inhibitors was attributed to the T cells rather than DC. Additionally, we analyzed the regulation of checkpoint molecules and their ligands on T cells and allogeneic DC in co-culture, which suggested a PD-1 blockade dependent crosstalk between T cells and APC. Our results indicate that several immune checkpoint inhibitors have the capacity to enhance T cell responses when combined with PD-1 blockade. Additional in vitro studies on human T cells will be useful to identify antibody combinations with the potential to augment T cell responses in cancer patients.